2005
DOI: 10.1038/sj.mp.4001737
|View full text |Cite
|
Sign up to set email alerts
|

Association of the calcyon gene (DRD1IP) with attention deficit/hyperactivity disorder

Abstract: Attention deficit/hyperactivity disorder (ADHD) is a childhood-onset disorder characterized by marked inattention, hyperactivity and impulsivity. The dopaminergic system has been hypothesized to be involved in the development of ADHD. Positive associations have been found for the dopamine receptors D1 and D5 genes, suggesting that other genes involved in D1/D5 signalling may also contribute to ADHD. In this study, we tested the calcyon gene (DRD1IP), which encodes a brain-specific D1-interacting protein involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…This is further supported by a large combined analysis of 14 independent samples of 1980 probands (P = 0.00005), odds ratio 1.24 (Lowe et al, 2004) for DRD5 (a D1-like receptor). In the same vein, we have recently reported evidence of association between ADHD and the calcyon gene, a D1-interacting protein (Laurin et al, 2005). D1/D5 signalling mediates executive abilities including working memory , attention (Bayer et al, 2000;Granon et al, 2000), motor control (Dreher and Jackson, 1989;Meyer, 1993), and reward and reinforcement mechanisms (Beninger and Miller, 1998).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is further supported by a large combined analysis of 14 independent samples of 1980 probands (P = 0.00005), odds ratio 1.24 (Lowe et al, 2004) for DRD5 (a D1-like receptor). In the same vein, we have recently reported evidence of association between ADHD and the calcyon gene, a D1-interacting protein (Laurin et al, 2005). D1/D5 signalling mediates executive abilities including working memory , attention (Bayer et al, 2000;Granon et al, 2000), motor control (Dreher and Jackson, 1989;Meyer, 1993), and reward and reinforcement mechanisms (Beninger and Miller, 1998).…”
Section: Introductionmentioning
confidence: 92%
“…The methods of assessment, characteristics of the subjects, and inclusion/exclusion criteria have been described previously, including the instruments used to collect information for the diagnosis of ADHD and co-morbid conditions (Barr et al, 1999;Laurin et al, 2005;Quist et al, 2000). Briefly, probands and their siblings between 7 and 16 years old were included if they met DSM-IV criteria for one of the three ADHD subtypes.…”
Section: Study Sample and Diagnostic Assessmentmentioning
confidence: 99%
“…But, whether or how altered calcyon expression might influence behavior in not known. Polymorphisms in the calcyon gene are associated with attention deficit hyperactivity disorder (ADHD) [8]. Additionally, a genome wide linkage scan for loci influencing in ADHD reported that the strength of association of a marker at 10q26, the cytogenetic position of the calcyon locus, significantly exceeded that of the DA transporter (DAT1), and the D4R (DRD4) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Before participating in the study, parents were queried as to whether their child had ever been diagnosed with ADHD, and any children identified as such were excluded from continuing in the present study, and were referred, instead, to a separate genetic study of ADHD. 33,[52][53][54] Following this prescreen for ADHD, children eligible for the present study underwent the full study assessment. Children were subsequently excluded from the study if they scored below 80 on both the verbal and performance domains of the Wechsler Intelligence Scale for Children-III (WISC-III).…”
Section: Methodsmentioning
confidence: 99%